Membangun Iman Melalui Pembelajaran Kolaboratif dalam Pembelajaran Pendidikan Agama Kristen - Surudiaman Lase; Iman Pasrah Zay; Adelia Tamo Ina; Sandra Rosiana Tapilaha (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study examines the strategic role of collaborative learning in strengthening students’ faith and character within the context of Christian Religious Education (CRE). In the face of globalization and the rapid development of digital technology, CRE is increasingly expected to go beyond the transmission of theological knowledge and actively nurture the application of Christian values in daily life. Employing a qualitative case study approach, the research includes classroom observations, semi-structured interviews, and document analysis involving both teachers and students engaged in collaborative learning. The results show that collaborative learning fosters active student engagement, character formation, improved social interaction, and a deeper understanding of spiritual values. Teachers are shown to play a critical role as facilitators, cultivating an inclusive and dialogical classroom environment. The study finds that this learning model effectively integrates faith development with critical thinking and interpersonal skills. The findings also underscore the importance of pedagogical innovation in CRE to better respond to the educational needs of a younger generation living in a diverse and digitally connected society. Therefore, collaborative learning can be viewed as a relevant and impactful strategy for renewing Christian education in today’s complex educational landscape.